Methodological Foundations for the Formation of Universal Educational Actions in the Context of the Ideas of the V.S. Mukhina's Concept "Phenomenology of Personality Development and Being" - V.S. Basyuk; S.V. Melkov (Moscow State University of Psychology and Education, 2024)
The article considers the methodological foundations for the formation of universal educational actions as the basis for the creation of metasubject results of general secondary education and it examines the key ideas of cultural-historical and system-activity approaches that are fundamental in achieving the main results of school education. The authors substantiate the importance of implementing these ideas at the level of federal state educational standards in order to systematize, standardize and regulate the activities of teachers in a modern school. The article also reveals the interrelation of the currently existing methodology for the formation of universal educational actions with the ideas of the concept of the V.S. Mukhina's scientific school «Phenomenology of personality development and being». Here’s also substantiated the productivity of considering V.S. Mukhina's scientific ideas on the mental mechanisms of identification-isolation and factors determining the development of the personality, including: 1 – genotypic prerequisites, as methodological foundations for the formation of cognitive, communicative and regulatory universal educational actions; 2 – external conditions (the reality of the objective world, the reality of figurative and symbolic systems, natural reality, the reality of the socio-normative space); 3 – the internal position of the personality. The authors consider the interrelation of personal educational outcomes with universal educational activities as well. They also defend the idea that the prior purpose of education is personal development.